2011
DOI: 10.1080/01635581.2011.563032
|View full text |Cite
|
Sign up to set email alerts
|

Oral Resveratrol Therapy Inhibits Cancer-Induced Skeletal Muscle and Cardiac Atrophy In Vivo

Abstract: The mechanism by which cancer mediates muscle atrophy has been delineated in the past 3 decades, and includes a prominent role of tumor-derived cytokines, such as IL-6, TNFα and IL-1. These cytokines interact with their cognate receptors on muscle to activate the downstream transcription factor NF-κB and induce sarcomere proteolysis. Experimentally, inhibiting NF-κB signaling largely prevents cancer-induced muscle wasting, indicating its prominent role in muscle atrophy. Resveratrol, a natural phytoalexin foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 56 publications
6
69
0
Order By: Relevance
“…By Days 18–19 of tumor growth, gastrocnemius muscle mass was 20% less and body weight was 5% less in tumor-bearing animals than in healthy control animals, confirming the targeted effect of tumor growth on lean body mass (Martin et al, 2013). These changes in body and gastrocnemius muscle weight were not due to anorexia–cachexia syndrome, as food and water intake of the tumor-bearing animals did not decline during the study period, a finding supported by previous reports (Graves et al, 2006; Shadfar et al, 2011; Xu et al, 2011). However, others have observed reduced food intake and up to 20% body weight loss in this mouse model of tumor-induced muscle wasting (Murphy et al, 2012; Tian et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…By Days 18–19 of tumor growth, gastrocnemius muscle mass was 20% less and body weight was 5% less in tumor-bearing animals than in healthy control animals, confirming the targeted effect of tumor growth on lean body mass (Martin et al, 2013). These changes in body and gastrocnemius muscle weight were not due to anorexia–cachexia syndrome, as food and water intake of the tumor-bearing animals did not decline during the study period, a finding supported by previous reports (Graves et al, 2006; Shadfar et al, 2011; Xu et al, 2011). However, others have observed reduced food intake and up to 20% body weight loss in this mouse model of tumor-induced muscle wasting (Murphy et al, 2012; Tian et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…This tumor cell line secretes interleukin 6 (IL-6) and TNF-α (Graves, Ramsay, & McCarthy, 2006) and does not metastasize when injected subcutaneously (Okayama et al, 2009). It is frequently used to model the systemic effects of tumor growth on skeletal muscle, heart, gut, and skin (Cosper & Leinwand, 2011; Murphy, Chee, Trieu, Naim, & Lynch, 2012; Redon et al, 2010; Shadfar et al, 2011; Tian et al, 2011). The gastrocnemius is most often used to study the effects of tumor growth on skeletal muscle because it contains both slow- and fast-twitch fibers.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, resveratrol has shown its protective effect on muscle wasting under diverse catabolic conditions including cachexia and disuse [48,49,53]. Besides this, resveratrol treatment shows its anti-cachectic role by inhibiting NFB activity and MuRF1 expression in MAC16 tumor and C26 adenocarcinoma bearing mice [54,55]. Studies have shown that resveratrol regulates TNF␣ induced atrophy by up-regulating the phosphorylation of Akt, p70S6K, mTOR and 4E-BP1 and protects the dexamethasone-induced atrophy by inhibiting the increase in atrogin1 and MuRF1 expression via activation of SIRT1 (sirtuin, a histone deacetylase) and PGC-1␣ [48,49].…”
Section: Resveratrolmentioning
confidence: 96%
“…Studies have shown that resveratrol regulates TNF␣ induced atrophy by up-regulating the phosphorylation of Akt, p70S6K, mTOR and 4E-BP1 and protects the dexamethasone-induced atrophy by inhibiting the increase in atrogin1 and MuRF1 expression via activation of SIRT1 (sirtuin, a histone deacetylase) and PGC-1␣ [48,49]. In streptozotocin induced diabetic rat model, resveratrol administration enhanced the insulin sensitivity, AMP-activated protein kinase (AMPK) and SIRT1 activities, and mitochondrial genesis and down-regulated the mRNA expression of pro-inflammatory cytokines (IL-1␤ and IL-6) and NFB expression [52,55]. Furthermore, resveratrol treatment for COPD decreases the levels of TNF␣ and increases the expression of SIRT1 which ultimately activates AMPK and regulates the muscle wasting [56].…”
Section: Resveratrolmentioning
confidence: 98%
“…Earliest evidence came from cardiac models in which resveratrol was shown to prevent atrophy through the inhibition of NF-κB (p65) [103,104]. Guided by these initial findings a number of newer investigations have shed light on the multi-faceted effects of resveratrol on muscle wasting genes.…”
Section: Natural Products Targeting F-box Family Proteins and Theimentioning
confidence: 99%